3x-7=7x-17

Simple and best practice solution for 3x-7=7x-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-7=7x-17 equation:


Simplifying
3x + -7 = 7x + -17

Reorder the terms:
-7 + 3x = 7x + -17

Reorder the terms:
-7 + 3x = -17 + 7x

Solving
-7 + 3x = -17 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-7 + 3x + -7x = -17 + 7x + -7x

Combine like terms: 3x + -7x = -4x
-7 + -4x = -17 + 7x + -7x

Combine like terms: 7x + -7x = 0
-7 + -4x = -17 + 0
-7 + -4x = -17

Add '7' to each side of the equation.
-7 + 7 + -4x = -17 + 7

Combine like terms: -7 + 7 = 0
0 + -4x = -17 + 7
-4x = -17 + 7

Combine like terms: -17 + 7 = -10
-4x = -10

Divide each side by '-4'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| 18.23=x+0.21*x | | 7x+13=97-6x | | 75-5x=8x+18 | | 11x-5x+1=-65x+36 | | 3(2x-3)-(4x-5)=0 | | 3x-11=75-5x | | 2x-3=7(x-2)4 | | 3*3-3*3=2 | | 5-5=5X+4X | | 5*9+5*4=280 | | 10W-17W=-49 | | -3-5=-6+X | | 3x(2)+7=5(3x+4) | | 3x+4*5=6 | | 3(x+9)(x-7)=0 | | -4x=17-5 | | A+(n-1)d=45 | | (x^2)+20x=800 | | (3xy+3)(5x^3y^2+2)=0 | | T^3-4t=-3 | | -5-7=10x+5-9x | | 196-14x=98-7x | | 4(2-1)-66=-5(2x+3) | | (-x+5)(7x-14)=0 | | 60x=x-3x | | -5x-2=x+4 | | 90-4x=2x+8 | | 4x+2.5=12.5+2x | | 35+x=14 | | 4x+2.55=12.5+2x | | -11x-4=14-9x | | 23-3n= |

Equations solver categories